SIKAP KERJA ADVOKAT PADA ORGANISASI PROFESIONAL - Tukinu Tukinu; Istiatin Istiatin; Supawi Pawenang (STIE Pelita Nusantara Semarang, 2020)
The objective of the research is to analyze the effect of professionalism, job satisfaction, and organizational commitment on job attitudes among members of Indonesian Advocate Congress (Kongres Advokat Indonesia/ KAI) in Solo Raya. The type of the research is survey research. The sample of the research uses non-probability census sampling. The data collection technique was done using questionnaire. The data analysis is done using multiple regression analysis. The research concluded that professionalism, job satisfaction, and organizational commitment affect the job attitudes among advocates both simultaneously and partially